Computational chemistry applications and new technologies - Abdulsalami, Ibrahim Olasegun; Adelani Alabi, Kazeem; Adeoye, Moriam Dasola; Aderinto, Shukurat Modupe; Adigun, Rasheed Adewale; Adigun, Temidayo Olamide; Akintemi, Eric O.; Alakanse, Oluwaseun Suleiman; Ambrose, George Oche; Bekono, Boris D.; Bello, Isa Adewale; Bhagwat, Archana; et al. (De Gruyter, 2021)
Computational Chemistry serves as a complement to experimental chemistry where the tools are limited. Using computational programs to solve advanced problems is widely used in the design and analysis of for example new molecules, surfaces, drugs and materials. This book will present novel innovations in the field, with real-life examples of where computational technologies serves as an indispensible tool.